HARTA BERSAMA DAN PERJANJIAN PERKAWINAN DALAM PUTUSAN MAHKAMAH KONSTITUSI NOMOR 69/PUU-XIII/2015 MENURUT PERSPEKTIF HUKUM ISLAM - Indah Purbasari; Moh. Syaifur Rijal (Trunojoyo Madura University, 2023)
Indonesian Constitution Court Verdict Number 69/PUU-XIII/2015 legitimates the rule on matrimonial property stated in Marriage Law. Meanwhile, it extends the intepretation of Pre-nuptial Agreement at which it can be held pre-marriage and/or during marriage. This verdict appears legal issue on the shariah compliance. The research used legal method by applying statute and conceptual approach. The result of this research found that Indonesian Constitution Court Verdict on matrimonial property has contradiction to The Islamic Law at which Al-Quran rules property ownership principle separately. Besides, The Verdict allows pre-nuptial agreement made before and/or during marriage has no shariah compliance. Pre-nuptial agreement can be analogically similar with the condition agreed before marriage. It means that pre-nuptial agreement must be consented before the declaration of marriage.